The Relationship Between Child Gender and Maternal Knowledge With the Incidence of Stunting in Toddlers - Usi Lanita (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Stunting is a chronic nutritional problem in toddlers that remains a global concern, including in Indonesia. This condition is characterized by height that is not appropriate for age due to long-term malnutrition, repeated infections, and environmental and social factors. The impact of stunting not only affects physical growth but also cognitive development, future productivity, and increases the risk of degenerative diseases in adulthood. Various factors contribute to stunting, including biological factors such as the child's gender and behavioral factors such as maternal knowledge about nutrition and health. This study aims to analyze the relationship between child gender and maternal knowledge and the incidence of stunting in toddlers. The research design used a quantitative cross-sectional approach. A sample of 73 respondents was selected using a stratified proportional sampling technique. Data collection was conducted through structured interviews using questionnaires and anthropometric measurements of toddlers. Data analysis was performed using univariate analysis to describe frequency distributions, and bivariate analysis using the chi-square test with a 95% confidence level. The results showed no significant association between child gender and stunting (p > 0.05). This indicates that biological factors such as gender are not the primary determinant of stunting in the study area. Conversely, there was a significant relationship between maternal knowledge and the incidence of stunting in toddlers (p < 0.05), indicating that mothers with low levels of knowledge are at greater risk of having stunted children. These findings emphasize the importance of improving maternal knowledge through ongoing nutrition education programs, health counseling, and promotive-preventive activities at community health centers. These interventions are expected to prevent stunting and other health problems in toddlers and support the achievement of the national stunting reduction target.